Bile Acids: Key Regulators and Novel Treatment Targets for Type 2 Diabetes - Yingjie Wu; An Zhou; Li Tang; Yuanyuan Lei; Bo Tang; Linjing Zhang (Journal of Diabetes Research)
Type 2 diabetes mellitus (T2DM), characterized by insulin resistance and unclear pathogenesis, is a serious menace to human health. Bile acids are the end products of cholesterol catabolism and play an important role in maintaining cholesterol homeostasis. Furthermore, increasing studies suggest that bile acids may regulate glucose tolerance, insulin sensitivity, and energy metabolism, suggesting that bile acids may represent a potential therapeutic target for T2DM. This study summarizes the metabolism of bile acids and, more importantly, changes in their concentrations, constitution, and receptors in diabetes. Furthermore, we provide an overview of the mechanisms underlying the role of bile acids in glucose and lipid metabolism, as well as the occurrence and development of T2DM. Bile acid-targeted therapy may represent a valid approach for T2DM treatment.